Pengaruh Literasi Keuangan dan Digital Terhadap Preferensi Bank Digital - Muhammad Basri; Muarif Leo (Journal of Trends Economics and Accounting Research, 2023)
Banking is a growing sector that can drive economic growth; by continuing to adapt, banks are adopting digital technology to survive. Currently, the challenges of the digital world are increasing. Banks must not only compete with other banks but also must be able to compete with other financial technology companies. One way to adapt and survive in this era is with the emergence of digital banks. The public must also be educated about these digital banking services because financial and digital literacy must be understood first. This research aims to find out and confirm the relationship between financial literacy and digital literacy with consumer preference for digital banks. This type of research is descriptive research with a quantitative approach using primary data. The results obtained are: Financial literacy partially affects consumer preferences for digital banks; Digital literacy partially affects consumer preferences for digital banks; Financial literacy and digital literacy simultaneously affect consumer preferences for digital banks. This research aims to contribute to the development of digital banks in Indonesia